Nerve supply of anterior cruciate ligaments and of cryopreserved anterior cruciate ligament allografts: a new method for the differentiation of the nervous tissues - Fromm, Bernd; Kummer, Wolfgang (Knee surgery, sports traumatology, arthroscopy, 1994)
We investigated the nerve supply of anterior cruciate ligaments ((ACLs) and of cryopreserved bone-ACL-bone allografts in a rabbit model with immunohistochemical methods to establish the distribution pattern of the nervous tissues and to determine the reinnervation rate of ACL allografts. The ACL is innervated by three different classes of nerve fibre: (1) fibres of large diameter, characterized by neurofilament immunoreactivity, which are fast-conducting mechanoreceptive sensory afferents; (2) fibres of small diameter, characterized by substance Pimmunoreactivity, which are slow-conducting nociceptive sensory afferents; and (3) sympathetic efferent vasomotor fibres, characterized by their immunoreactivity to the ratelimiting enzyme of noradrenaline synthesis, tyrosine hydroxylase. The ACLs showed numerous fibres of all three nerve classes; as specialised sensory nerve endings only Ruffini corpuscles were observed. All nerve fibres were located subsynovially, none within the collagen core of the ligament itself. No nerve fibres were detected in the ACL allografts at 3 and 6 weeks. Sparse fibres were detected at 12 weeks, while the 24-, 36-and 52-week specimens showed plenty of all three fibre types. No mechanoreceptors were found in the ACL allografts. To our knowledge, this method for the first time allows a differentiation of the nerve fibres of ACLs and ACL allografts into three different nerve fibre classes with known neurophysiological functions.